Visual environment as an important environmental factor - Tolstaya, Elena V.; Kozelko, Nina A. (Journal of the Belarusian State University. Ecology, 2019)
The review shows that the visual (visible) environment around us is one of the important environmental factors affecting human health. The artificial visible environment, primarily urban, is significantly different from the natural and often contradicts the physiology of visual perception. Violation of the visual environment of a person, manifested in an abundance of homogenic and aggressive fields, as well as in an unnatural color environment, leads not only to disruption of the organ of vision, but also contributes to the development of mental disadaptation. The environment is saturated with various visual characteristics that can either mitigate the influence of other negative environmental factors or, conversely, aggravate the ecological situation.